Global optimization of the value chain - Tallman, Stephen (Henry Stewart Talks, 2014)
The value chain and the traditional MNE, Value chain dispersion and optimization (drivers and facilitators, location, and ownership & control), Dispersing value creation in manufacturing and services, Building the global network firm (strategic assembly & animation)
Updated at 2014/04/06